2015
DOI: 10.18579/jpcrkc/2015/14/1/78368
|View full text |Cite
|
Sign up to set email alerts
|

Central Composite Designed Taste Masked Ion Exchange Resinates for Development of Azithromycin Dispersible Tablets

Abstract: ABTRSACT Purpose:The purpose of the present investigation was to formulate taste masked dispersible tablets of azithromycin using complexation by ion exchange resin applying the central composite design. Methodology:The basic methodology behind the present work was the application of ion exchange resin complexation for masking the bitter taste of azithromycin. The central composite design (CCD) was applied to study the effect of two critical factors i.e. swelling time (X ) and stirring time (X ) on percent dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Recent studies have reported that more than a half of the interviewed patients with schizophrenia (n = 400) preferred orally disintegrating tablets (ODT) to other dosage forms, such as tablets, for swallowing or oral delivery. [5][6][7] In this sense, other forms of delivery, such as the use of chewable or dissolvable tablets, [8][9][10] or rapidly dissolving films, [11][12][13] could be advantageous; however, these forms must be preceded by the development of taste-masking formulations, owing to the unpleasant taste of APZ. Numerous approaches have been employed in the field of taste masking, most of which were have been based on the encapsulation of drugs inside polymeric materials, such as hydroxypropylmethylcellulose (HPMC), Eudragit EPO, and Abstract: Poor aqueous solubility and the unpleasant taste of aripiprazole (APZ) have been recurring problems, owing to its low bioavailability and low patient tolerance, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that more than a half of the interviewed patients with schizophrenia (n = 400) preferred orally disintegrating tablets (ODT) to other dosage forms, such as tablets, for swallowing or oral delivery. [5][6][7] In this sense, other forms of delivery, such as the use of chewable or dissolvable tablets, [8][9][10] or rapidly dissolving films, [11][12][13] could be advantageous; however, these forms must be preceded by the development of taste-masking formulations, owing to the unpleasant taste of APZ. Numerous approaches have been employed in the field of taste masking, most of which were have been based on the encapsulation of drugs inside polymeric materials, such as hydroxypropylmethylcellulose (HPMC), Eudragit EPO, and Abstract: Poor aqueous solubility and the unpleasant taste of aripiprazole (APZ) have been recurring problems, owing to its low bioavailability and low patient tolerance, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, the nanohybrids could be the base formulation for ODTs, which are the most favoured form of oral delivery by schizophrenia patients. [5][6][7] To accomplish taste masking, the release of the drug from the nanohybrids at the buccal cavity should be greatly suppressed. On the contrary, for enhanced drug bio-A C H T U N G T R E N N U N G availability, the release of the drug from the nanohybrids should be rapid and efficient, at least comparable to other commercially available medication, Abilify , through the gastrointestinal (GI) tract.…”
mentioning
confidence: 99%
“…Slow discharge of the drug results into taste-masking due to drug is present in minimal and below the bitterness threshold in the oral cavity. In this analysis, the drug is analyzed from the dissolution media of phosphate buffer (pH 6.8) at concentrations below its bitterness threshold [43][44][45][46][47]. Threshold bitterness concentration is the lowest concentration that had a bitter taste.…”
Section: In Vitro Taste Evaluation Studymentioning
confidence: 99%